Eurovision and the City: “United by Music” Meets “Malmö against Genocide” - Myrto Dagkouli-Kyriakoglou; Adriana de La Peña; Laleh Foroughanfar; Jennie Gustafsson; Lorena Melgaço; Chiara Valli (Urban Planning)
“United by Music” was the slogan of the 2024 edition of the Eurovision Song Contest, held in Malmö. However, the festive spirit of the event oddly contrasted with what was described as “the largest police operation in Sweden’s history” (Ivarsson, 2024). This operation was mobilized in response to the expected civil protests regarding Eurovision’s decision to welcome Israel’s participation, despite its ongoing genocidal war on Gaza. We examine the temporary disruptions in Malmö’s urban space during Eurovision to understand the dissonance between a peaceful pro‐Palestine movement, a supposedly festive event, and the heightened securitization of the city with its alarmist tones. We aim to understand these contrasts within a broader temporal context and across different geographical scales. We argue that the distinct racialized characterizations of neoliberal authoritarian practices in Malmö during Eurovision are deeply enmeshed with the implications of the Western narratives about Israel and Palestine, the growing influence of the far‐right in Swedish politics, and, ultimately, the identity Malmö aspires to and is perceived to have. Rather than being a local manifestation of isolated authoritarian practices, Eurovision in Malmö opens a conceptual space to explore authoritarianism as a multiscalar discourse and practice. This perspective allows us to move beyond the dichotomy of the “democratic West” versus the “authoritarian others” by revealing the persistence of authoritarian practices in democracies.